2014
DOI: 10.1007/s12032-014-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of circulating monocytes and lymphocyte-to-monocyte ratio on previously untreated metastatic non-small cell lung cancer patients receiving platinum-based doublet

Abstract: The link between circulating lymphocyte-to-monocyte ratio (LMR) and newly diagnosed metastatic non-small cell lung cancer (NSCLC) is not fully defined. The study was conducted to evaluate the prognostic impact of LMR on survival outcomes in previously untreated metastatic NSCLC patients receiving platinum-based doublet. Chemotherapy-naive metastatic NSCLC patients undergoing platinum-based doublet were retrospectively enrolled. Clinical features regarding gender, age, Eastern Cooperative Oncology Group (ECOG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 25 publications
4
49
1
Order By: Relevance
“…Twenty-one studies provided sufficient data for the meta-analysis of the correlation between LMR and clinicopathological characteristics (Table 3) [10, 2224, 2932, 37, 39, 42, 43, 46, 51, 5861]. Urothelial carcinoma, esophageal cancer, gastric cancer, renal cell carcinoma, lung cancer, DLBCL and Hodgkin's lymphoma were investigated in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies provided sufficient data for the meta-analysis of the correlation between LMR and clinicopathological characteristics (Table 3) [10, 2224, 2932, 37, 39, 42, 43, 46, 51, 5861]. Urothelial carcinoma, esophageal cancer, gastric cancer, renal cell carcinoma, lung cancer, DLBCL and Hodgkin's lymphoma were investigated in detail.…”
Section: Resultsmentioning
confidence: 99%
“…LMR, one of the inflammatory biomarkers, was regarded as an independent prognostic factor for DFS and OS in previously untreated metastatic NSCLC patients receiving platinum-based doublet chemotherapy 33. However, Song et al34 found that the LMR values at initial diagnosis and disease progression were similar in patients with early-stage NSCLC ( P =0.287), which suggested that LMR would not be predictive of DFS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous revealed LMR was prognostic factor in early-stage malignancies including lung cancer[38], and nasopharyngeal carcinoma [39]; in advanced-stage malignancies including diffuse large B-cell lymphoma [40, 41], lung cancer patients receiving chemotherapies[42], and breast cancer patients receiving neo-adjuvant chemotherapies. [43] Our study revealed that patients with de novo bone metastases had better prognosis if they had higher baseline blood LMR ratio.…”
Section: Discussionmentioning
confidence: 99%